КРИТЕРІЇ НЕОБХІДНОЇ ТА ДОСТАТНЬОЇ КІЛЬКОСТІ ІТЕРАЦІЙ ФІЛЬТРАЦІЇ НЕПЕРІОДИЧНИХ НЕСТАЦІОНАРНИХ СИГНАЛІВ БАГАТОІТЕРАЦІЙНИМИ МЕТОДАМИ - Шидловська, Н.А.; Захарченко, С.М.; Черкаський, О.П. (Інститут електродинаміки НАН України, Київ, 2017)
An analysis of efficiency of procedure-oriented criteria for determining the required number of filtration iterations of non-stationary non-periodic signals by the multi-iterative method of the moving average with an increasing width of the filtering window on an instance of pulses of voltage on the plasma-erosive load and of current in it had fulfilled. Two main groups of criteria are considered which are based on a comparison of the signal at the current iteration of its filtering either with the signal at the previous iteration or with a reference signal. Also criterion which has properties of criteria of both these groups is considered. The low effectiveness and nonuniversality of the known criteria is shown. New objectively-oriented criteria for the necessary and sufficient number of iterations of filtering non-stationary nonperiodic signals, adaptive to the requirements for further signal processing, are proposed and an analysis of their effectiveness had fulfilled. References 13, figures 2, tables 4.